ANALISIS PENGARUH PENGETAHUAN, KETERAMPILAN, SIKAP, MOTIVASI DAN PENGALAMAN KERJA TERHADAP KINERJA KARYAWAN PADA PERUSAHAAN PY. PELNI CABANG MAKASSAR - ST. Nafilah; Djabir Hamzah; Nuraeni Kadir (Program Studi Akuntansi Universitas Kristen Indonesia Paulus, 2023)
This study aims to determine and analyze the effect of knowledge, skills, attitudes, motivation and work experience on employee performance at PT. PELNI Makassar Branch. The population in this study are employees at PT. Pelni Makassar Branch, totaling 43 people. To apply these objectives, data collection techniques are used by distributing questionnaires. While the data analysis technique uses multiple linear regression analysis. The results of the study found that knowledge, skills, attitudes, motivation and work experience partially had a positive and significant effect on employee performance at PT. PELNI Makassar Branch. Then from the results of testing the hypothesis, it is known that the dominant variable influences the performance of employees at PT. Pelni Makassar Branch is a work experience. This is because work experience has the highest regression coefficient value, and has a smaller significant value than the other variables.